WEBSITE DEVELOPMENT FOR SMART FOOD STORAGE AND WASTE MANAGEMENT - Dr. A. S. Budhewar, Ms. Bhakti S. Dhavalsank, Ms. Radhika A. Asapure, Ms. Sanyogeeta M. Jagtap, Ms. Tajmin I. Bagwan. (International Journal of Innovations in Engineering Research and Technology, 2022)
Greenhouse gases are emitted at food production time (which makes the 14.1% of emission) while methane gas is produced at the time of food decay [1]. Food production consumes water as one apple growth consumes 125 litres of water and one-kilogram beef needs to consume 15,400 litres [2]. And a huge amount of food waste contributes to water waste. According to [3], 3.3 billion tons of CO2 wasted each year, and 1 tons of food waste reduction can save approximately 4.2 tons of CO2 [4]. To overcome the problem of food waste management we have developed a website which gives us detail information about the NGO’s that distribute the food among the poor people. In the world full of junk food, we need to keep ourselves healthy we provide the information about the healthy grains you need to include in your diet. The main feature of the website is that our website provides the accurate list of the item you need to make a specified item. So that you can make the food for the specified number of people.